Taktyka prezydenta Paulusa Krugera wobec Wielkiej Brytanii w latach 1883-1900 - Matera, Rafał (Acta Universitatis Lodziensis. Folia Historica, 1999)
Paulus Kruger (1825-1904) was a co-founder of the first Boer State and four times President of Transvaal State in the years 1883-1900. As a young boy he took part in the Great Trek which led to the establishment of the new Boer republics in South Africa. He assumed the main duties in Transvaal and after British annexation in 1877 Kruger visited twice London to talk about the restoration of Transvaal’s independence. After his return to South Africa he was the leader of the first Boer War, which led to Transvaal autonomy under British „suzerainty”. From the very beginning of his presidency the most important purpose for Kruger was to establish the relationships with the United Kingdom. His third visit in London in 1884 brought the signing of the new London Convention. The convention granted sovereignty to Transvaal but South African Republic (new name of the state) could not pursue its own foreign policy except for maintaining relations with Orange Free State. It was difficult for Kruger to achieve self-dependence in Transvaal’s policy especially since the shrewd politician, Cecil John Rhodes had arrived to South Africa. During Kruger’s presidency there was a bitter dispute over Boer-British controversy about Swaziland and Matabeland in the North of Transvaal. The most burning issue in Boer-British relations was to solve the problem of „uitlanders” who had come to South Africa after the discovery of gold and diamond fields. The British tried to organise an opposition against Boer rules but the Jameson raid at the end of 1895 ended in failure. Soon afterwards Kruger received congratulations from William II but German support lasted short and in the years to follow Germany entered into friendly relations with Great Britain. At the end of 90s Kruger was no longer able to oppose British demands. The conference in Bloemfontein in June 1899 was the last attempt to save the peace but Alfred Milner’s and Joseph Chamberlain’s demands were too unreasonable to be accepted. On the 9th of October 1899 Kruger with Volksraad (Transvaal’s parliament) made up their minds about ultimatum to Great Britain. It meant that the war was bound to commence. The one and only ally for South African Republic was Orange Free State. Kruger ceased to be the President in September 1900 after British annexation during the second Boer War. Despite the fact that Kruger was no longer the president, he went to Europe at the end of 1900 but he failed in his efforts, to receive the support from Germany, France or Holland. He did not want to talk to the London government either. There was no possibility to change the British attitude to the Boer republics’ future. Kruger died in exile in Switzerland without ever seeing his free country again.